Gravitational Waves or Electromagnetic Waves? How they Influence us? (Global Journal of Science Frontier Research, 2019)
Our science became too much differentiated and the different branches of science do not communicate with each other. It is like each organ of the body functioning on its own. If we want to see how the body functions, we need to see the global picture – how the different organs are internally dependent in their functioning. Analogically, if we want to see the global picture of how the Universe was created and functions, we need to start integrating the different branches of science. For example, the turbulence studied in oceanology1,2 might be very useful to see what is going on in the Universe. The observed turbulence is the same, only the density of the media is different. The so-called double eddies recently studied in oceanography, are nothing else but a vortex next to an anti-vortex. Why are double eddies formed? Let us recall the rule of the folded fingers of the right hand in physics, which states that if the folded fingers are in the direction of the electric currents (or spinning), the vertical thumb shows the direction of the induced magnetic field.